2021
DOI: 10.3390/vaccines9060639
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Genetic Variability and Non-Specific Immunity Associated with the Use of Different BCG Strains—A Molecular and Clinical Approach

Abstract: The effect of BCG vaccination against tuberculosis on the reduction in COVID-19 infection is related to the effect of the BCG vaccine on the immunomodulation of non-specific immunity. In the early stages of the pandemic, countries with universal BCG vaccination programs registered a low number of new cases of COVID-19, with the situation now reversed, as exemplified by India. The high genetic variability of SARS-CoV-2, a known characteristic of RNA viruses, causing the occurrence of SARS-CoV-2 variants may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 113 publications
(178 reference statements)
0
4
0
Order By: Relevance
“…The sheep were also vaccinated against Johnes disease with a multivalent vaccine (Glanvac 6 in 1 or equivalent), to control five clostridial diseases and Caseous Lymphadenitis, which may have provided extra immuno-stimulatory properties. Protection against SARS-CoV-2 has been suggested with non-specific vaccination approaches, such as with BCG vaccine against tuberculosis 33 . This approach was tested in a non-human primate model and showed that BCG vaccination induced heterologous immune mechanisms which could contribute to moderating SARS-CoV-2 disease severity, although there was no evidence of enhanced viral clearance or reducing disease pathology 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The sheep were also vaccinated against Johnes disease with a multivalent vaccine (Glanvac 6 in 1 or equivalent), to control five clostridial diseases and Caseous Lymphadenitis, which may have provided extra immuno-stimulatory properties. Protection against SARS-CoV-2 has been suggested with non-specific vaccination approaches, such as with BCG vaccine against tuberculosis 33 . This approach was tested in a non-human primate model and showed that BCG vaccination induced heterologous immune mechanisms which could contribute to moderating SARS-CoV-2 disease severity, although there was no evidence of enhanced viral clearance or reducing disease pathology 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals vaccinated with BCG in the past five years reported lower incidence of illness and fatigue compared to BCG non-vaccinated subjects 37 and anti-SARS-CoV-2 IgG seroprevalence and selfreported COVID-19 symptoms were significantly less in healthcare workers with BCG vaccination history 38 . In contrast, other studies do not report similar benefits 39,40 perhaps due to the timing of BCG vaccination prior to SARS-CoV-2 exposure or the BCG strain used [41][42][43] .…”
Section: Introductionmentioning
confidence: 83%
“…Differences in data analyses might be caused by using different BCG vaccine strains in different countries -their inequality in COVID-19 protection is postulated by one commentary article [24]. Then, the other research group confirmed those inter-strain differences with adaptive potential from the novel SARS-CoV-2 variants to omit post-BCG immune effects [29]. It corresponds with past reports suggesting different efficacy of BCG strains in both tuberculosis and urinary bladder therapy [48,49], and in its heterogenous effect on innate immunity [50].…”
Section: Bcg Strains and Administration Waysmentioning
confidence: 96%
“…Although comparisons between countries (from this period at least) seem to be unreliable due to different lockdown laws and different pandemic awareness level, this report and many similar in scientific literature had a crucial influence on research importance. The most recent data analyses reports that BCG-vaccination impact on COVID-19 pandemics was statistically significant, but only at the beginning of the pandemic [28,29].…”
Section: Epidemiological Datamentioning
confidence: 99%